P196 CHANGE IN THE DAILY HOSPITALIZATION RATE FOR ACUTE MYOCARDIAL INFARCTION IN THE VENETO REGION FROM 2006 TO 2018. (18th May 2022) - Zuin, M; Picariello, C; Anselmi, M; Roncon, L; Bilato, C
Abstract: Background: Acute myocardial infarction (AMI) continues to represent the leading cause of cardiovascular mortality in Italy, with important prognostic and health consequences both in the short and long term. The aim of the study is to evaluate the long–term variation in the daily hospitalization rate for AMI in the Veneto region. Materials and Methods: Data regarding the total number of hospitalizations due to AMIbetween 2006 and 2018 were extracted from the periodic epidemiological reports of the Veneto region which can be consulted on the website www.ser–veneto.it and then re–elaborated and analyze. In particular, changes in daily hospitalization rates for AMI were calculated, then sub–classified into AMI with ST–segment elevation myocardial infacrction (STEMI) and without (NSTEMI). The trend of change in daily hospitalization rates was assessed with the Jonckheere–Terpstra test, using the SPSS statistical software version 19.0 (SPSS; SPSS Inc., USA). Results: During the study period, in the Veneto region 87, 490 hospitalizations for AMI [48, 165 (55.0%) STEMI and 32, 325 (45.0%) NSTEMI], of which 75.7% were managed in Cardiology / ICU wards were registered. The overall average daily hospitalization rate for AMI over the entire period was 18.3 ± 0.6 admissions / day [range 17.5 / 19.8] with a decrease of 11.4% / year (p = 0.009). Among these, patients admitted for STEMI were hospiutalized for 10.1 ± 1.2 / day [range 8.6–12.4]; however their daily hospitalization rate decreased by 32.4% / year (p < 0.001). Conversely, 8.2 ± 0.8 patients with NSTEMI / day were hospitalized in the observation period [range 7–8.9]. showing a growing hospitalization trend in the period considered (+ 20.9% / year, p < 0.001) (Figure 1 ). Conclusions: The daily hospitalization rate for AMI in the Veneto region has overall decreased in recent years, however, there has been a significant increase in daily hospitalizations for NSTEMI. The high number of daily hospitalizations requires close synergy between the cardiology departments of the region in order to ensure adequate care for patients with acute cardiac events in the area.